2019
DOI: 10.1039/c9ra08992f
|View full text |Cite
|
Sign up to set email alerts
|

A step forward in the development of superoxide dismutase mimetic nanozymes: the effect of the charge of the surface on antioxidant activity

Abstract: Binuclear Cu2+ complexes of a pyridinophane polyamine ligand grafted to boehmite nanoparticles show a remarkable increase in SOD activity, which can be ascribed to the positive ζ-potential of the nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 61 publications
(86 reference statements)
0
11
0
Order By: Relevance
“…À to the active centers, consistent with the active sites of natural enzymes. 128 However, there are few studies on the use of natural enzyme active centers to guide the activity of nanozymes, and we look forward to the review of this article to provide more ideas for future. For example, the active centers of SOD are mostly composed of metal ions coordinated by C, N, O and other elements of surrounding amino acids.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…À to the active centers, consistent with the active sites of natural enzymes. 128 However, there are few studies on the use of natural enzyme active centers to guide the activity of nanozymes, and we look forward to the review of this article to provide more ideas for future. For example, the active centers of SOD are mostly composed of metal ions coordinated by C, N, O and other elements of surrounding amino acids.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…20 Although to the best of our knowledge very few of such systems have shown a satisfactory clinical effect, 3,11,21 tetraazamacrocycles, on the one side, and nanotechnology, on the other one, are arising as potential therapeutics for neurodegenerative disorders where oxidative stress is involved. 15–18,22–25 In this context, we have recently found that decoration of non-toxic boehmite nanoparticles (BNPs) with binuclear Cu 2+ azamacrocycles leads to a striking enhancement of the SOD activity of such complexes. 23,24,26 It should be finally taken into account that, despite the high value of the catalytic constant shown by the above-mentioned SOD mimetics, if they are not able to revert the generation of mHTT aggregates, such SOD scavengers would be of little use in the treatment of HD.…”
mentioning
confidence: 99%
“…15–18,22–25 In this context, we have recently found that decoration of non-toxic boehmite nanoparticles (BNPs) with binuclear Cu 2+ azamacrocycles leads to a striking enhancement of the SOD activity of such complexes. 23,24,26 It should be finally taken into account that, despite the high value of the catalytic constant shown by the above-mentioned SOD mimetics, if they are not able to revert the generation of mHTT aggregates, such SOD scavengers would be of little use in the treatment of HD. 21 Though some successful attempts have been done in this sense for Alzheimer, 27 scarce success has been achieved for HD.…”
mentioning
confidence: 99%
See 2 more Smart Citations